A review study of maintenance and management issues in Malaysian commercial building towards sustainable future practice - Mohd Nasrun, Mohd Nawi; Faizal, Baharum; Siti Halipah, Ibrahim; Riazi Mehdi, Riazi (American Institute of Physics Inc., 2017)
Good management of the building will be able to influence the quality of the buildings that remain long, safe and beautiful without any damage and problems. This research paper aims to explore the issue of maintenance and management that appear in managing the commercial building in Malaysian construction and property industry. The data in this research has been gathered through the reviewing process of secondary data such as journals, proceeding, thesis etc. in the area that related to maintenance and management issue in commercial building. As highlighted by previous study, building a good management can ensure that the facilities available in the building are well and meet the standard. Thus, exposure to the problems and needs in the management of the building would be able to improve the quality of building management systems to be more effective and fulfil the client needs and features.